Evaluation of Upper Structure Strengthening Due to The Level Addition Based on SNI 2847-2013 Regulation: (Case Study: PNJ Heavy Equipment Building) - Vidia Intan Deliani; Agyanata Tua Munthe (NAROTAMA UNIVERSITY, Indonesia, 2021)
The number of college students, who came to Java Island especially Jakarta City, makes the availability of land will be limited, one who get affected is campus building. The solution that can be done is increase the level of building and evaluate the structural elements ability of existing building. This study aims to determine the effect of additional levels on the internal forces and dimensions of the upper structure and evaluate the conducted by analyzing existing building and building that have been added level using ETABS software which refers to SNI 2847-2013 regulations. The results showed that after the addition of level, moments and shear forces on beam increase averaging 43%, while the column increase averaging 22%. In column axial forces have increased averaging 47%. After the addition of level, structure of Heavy Equipment building is known that there are several structural components which is not strong enough to withstand the load, namely Beams B, B1, and RB consecutively as much as 6 frames, 26 frames, and 12 frames; Columns K, K1, and K2 consecutively as much as 18 frames, 12 frames, and 8 frames. Both beams and columns were strengthened by FRP (Fiber Reinforcement Polymer) so the dimensions of the beams and columns did not change. The strengthening of structural elements is as follows: Beams B, B1, and B2 are strengthened with FRP tensile strength of 2800 MPa, FRP thickness of 1,2 mm, FRP width of 80 mm and the number of FRP used is 1 layer. Columns K, K1, and K2 are strengthened with FRP tensile strength of 4300 MPa, FRP thickness of 0,167 mm, FRP width of 500 mm and the number of FRP used is 16 layer for columns K&K2 and 24 layer for column K1.